Deuterium-containing polymer as well as preparation method and application thereof

By introducing deuterium atoms and D-A-D structural design into electrochromic materials, the shortcomings in existing materials in terms of response speed, coloring efficiency and stability are solved, and higher performance electrochromic polymers are achieved.

CN119638962AActive Publication Date: 2025-03-18WUYI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411552874.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-18
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Existing electrochromic materials have challenges in cost, lifespan, response speed and environmental stability, and are difficult to meet the needs of future development.

Method used

Using deuterium-containing polymers, the electrochromic properties of the polymer are improved by introducing deuterium atoms and specific donor-acceptor-donor (D-A-D) structure design.

Benefits of technology

Improves the response speed and coloring efficiency of the polymer, achieves faster color changes and higher optical transmittance, and enhances the chemical stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638962A_ABST
    Figure CN119638962A_ABST
Patent Text Reader

Abstract

The invention provides a deuterium-containing polymer as well as a preparation method and application thereof. The polymer provided by the invention is based on a polymer containing a deuterium acceptor unit, i.e., an isotope-deuterium atom of a hydrogen element is introduced to a benzene ring or an anthracene ring of the electron acceptor unit, and a thienyl derivative is used as a terminal donor unit. The deuterium-containing polymer disclosed by the invention has good electrochromic performance, such as the characteristics of short response time, good optical transmittance, good stability and the like, and has wide application in preparation of electrochromic devices. The invention also provides a preparation method and application of the deuterium-containing polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a deuterium-containing polymer and a preparation method and application thereof. Background Art

[0002] In recent years, with the development of portable electronic devices, energy storage devices that can display working status have become increasingly important. The electrochromic phenomenon is based on the influence of electrochemical reactions or electric fields on the electronic structure of materials. Under the action of the electric field, the redox state of the material changes, causing changes in its optical properties. This change is usually manifested as a change in color, including a change in transmittance.

[0003] Electrochromic materials can be divided into two categories: inorganic materials (such as tungstates and vanadates) and organic materials (such as electrochromic polymers). Inorganic electrochromic materials usually have higher stability and faster response speed, while organic electrochromic materials have advantages in flexibility and processability, which makes electrochromic technology widely used in many fields, such as smart windows, car rearview mirrors, display technology, aerospace, etc.

[0004] Although electrochromic technology has a wide range of application potential, it still faces some challenges, such as material cost, lifespan, response speed and environmental stability. Future research will focus on improving material performance, reducing costs and expanding application areas to promote the further development and popularization of electrochromic technology.

[0005] Therefore, exploring and developing electrochromic polymers with new structures is a problem that needs to be solved today. Summary of the invention

[0006] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a deuterium (D)-containing polymer. The deuterium-containing polymer introduces deuterium, an isotope of hydrogen atoms, and a specific donor-acceptor-donor (DAD) structure design, which can improve the electrochromic properties of the polymer, such as coloring efficiency, response time, etc.

[0007] The invention also provides a method for preparing the deuterium-containing polymer.

[0008] The invention also provides an electrochromic material.

[0009] The invention also provides an application of a deuterium-containing polymer in preparing an electrochromic device.

[0010] In order to achieve the above object, the technical solution adopted by the present invention is:

[0011] The first aspect of the present invention provides a deuterium-containing polymer having a structure as shown in any one of formula (I) to formula (IV):

[0012]

[0013] In formulas (I) to (IV), X1 to X4 are each independently O, S, or Se; Y1 to Y8 are each independently O or S; R1 to R4 are each independently C2 to C 12 Alkyl; n1-n4 are each independently 3-200.

[0014] The technical solution of the deuterium-containing polymer of the present invention has at least the following beneficial effects: the introduction of deuterium helps to improve the ion migration rate of the electrochromic polymer, and the deuterium-containing polymer of the present invention can improve the response speed (T ox =0.1s), making it possible to achieve color changes faster in applications.

[0015] According to some preferred embodiments of the present invention, X1-X4 are each independently S.

[0016] According to some preferred embodiments of the present invention, Y1-Y8 are each independently O.

[0017] According to some preferred embodiments of the present invention, R1 to R4 are each independently C5 to C 10 alkyl.

[0018] According to some more preferred embodiments of the present invention, R1 to R4 are each independently C 10 H 21 .

[0019] According to some specific embodiments of the present invention, the deuterium-containing polymer has a structure as shown in any one of formulas (1) to (4):

[0020]

[0021]

[0022] In formulae (1) to (4), n1 to n4 are each independently 3 to 200.

[0023] The second aspect of the present invention provides a method for preparing the deuterium-containing polymer described in the first aspect of the present invention, comprising the following steps: subjecting an active precursor of the deuterium-containing polymer to an electrochemical polymerization reaction to obtain the deuterium-containing polymer, wherein the active precursor of the deuterium-containing polymer has a structure shown in any one of formula (I') to formula (IV'):

[0024]

[0025] In formulae (I') to (IV'), X1 to X4, Y1 to Y8 and R1 to R4 are as defined above.

[0026] The preparation method of the present invention does not require expensive equipment and complicated process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.

[0027] According to some embodiments of the present invention, the method for preparing the active precursor comprises: in the presence of a catalyst, performing a cross-coupling reaction between an acceptor compound and a donor compound in a solvent to obtain the active precursor;

[0028] The receptor compound is:

[0029] The donor compound is:

[0030] The catalyst comprises tetrakistriphenylphosphine palladium (Pd(PPh3)4) and / or bistriphenylphosphine palladium dichloride (Pd(PPh3)2Cl2);

[0031] The solvent includes at least one of benzene, toluene or N,N-dimethylformamide (DMF).

[0032] According to some embodiments of the present invention, in the method for preparing the active precursor, the solvent includes toluene and N,N-dimethylformamide.

[0033] According to some preferred embodiments of the present invention, in the method for preparing the active precursor, the volume ratio of toluene and N,N-dimethylformamide in the solvent is (3-5):1, for example, about 4:1.

[0034] According to some embodiments of the present invention, in the method for preparing the active precursor, the molar ratio of the acceptor compound to the donor compound is 1:(2-3), for example, about 1:2.5.

[0035] According to some embodiments of the present invention, in the method for preparing the active precursor, the molar ratio of the acceptor compound to the catalyst is 1:(0.01-0.1), and more preferably 1:(0.03-0.05).

[0036] According to some embodiments of the present invention, in the method for preparing the active precursor, the volume ratio of the molar amount of the acceptor compound to the solvent is 1 mmol: (50-200) mL, for example, about 1 mmol: 100 mL or about 1 mmol: 150 mL.

[0037] According to some embodiments of the present invention, in the method for preparing the active precursor, the temperature of the cross-coupling reaction is 100-140°C; more preferably 110-130°C, for example about 120°C.

[0038] According to some embodiments of the present invention, in the method for preparing the active precursor, the time of the cross-coupling reaction is 24 to 72 hours; more preferably 36 to 60 hours, for example about 48 hours.

[0039] According to some embodiments of the present invention, in the method for preparing the active precursor, a purification step is further included after the cross-coupling reaction; more preferably, the purification method is chromatographic separation purification.

[0040] According to some embodiments of the present invention, the chromatographic column used for the chromatographic separation and purification is selected from a silica gel column.

[0041] According to some embodiments of the present invention, the eluent used for the chromatographic separation and purification includes dichloromethane (DCM) and petroleum ether (PE); further preferably, the volume ratio of dichloromethane to petroleum ether is 1:(1-3), for example, about 1:2.

[0042] In the preparation method of the active precursor of the present invention, the cross-coupling reaction is a Stille or Suzuki palladium-catalyzed cross-coupling reaction, through which an active precursor based on a deuterium intermediate, namely, an active precursor represented by formula (I') to (IV'), can be prepared.

[0043] According to some embodiments of the present invention, in the method for preparing the active precursor, the cross-coupling reaction is carried out in an inert gas atmosphere. In a specific embodiment of the present invention, the inert gas is selected from nitrogen.

[0044] According to some embodiments of the present invention, the electrochemical polymerization reaction includes using a solution containing the active precursor as an electrolyte solution, performing electrodeposition in a three-electrode system consisting of a reference electrode, a counter electrode and a working electrode, and obtaining the polymer on the working electrode.

[0045] According to some embodiments of the present invention, the solvent of the electrolyte solution includes at least one of dichloromethane (CH2Cl2), chloroform (CHCl3) or acetonitrile (MeCN).

[0046] According to some embodiments of the present invention, the electrolyte solution further contains a supporting electrolyte.

[0047] According to some embodiments of the present invention, the supporting electrolyte includes at least one of tetrabutylammonium hexafluorophosphate (PF6), tetrabutylammonium tetrafluoroborate (BF4) or lithium perchlorate.

[0048] According to some embodiments of the present invention, the concentration of the active precursor in the electrolyte solution is 0.0005 to 0.01 mol·L -1 ; For example, about 0.001 mol·L -1 or about 0.005 mol·L -1 .

[0049] According to some embodiments of the present invention, the concentration of the supporting electrolyte in the electrolyte solution is 0.01 to 0.2 mol·L -1 ; For example, about 0.05 mol·L -1 , 0.1 mol·L -1 or about 0.15 mol·L -1 .

[0050] According to some embodiments of the present invention, the reference electrode is selected from Ag / AgCl electrode.

[0051] According to some embodiments of the present invention, the counter electrode is selected from a platinum electrode.

[0052] According to some embodiments of the present invention, the working electrode is selected from Pt, glassy carbon or ITO conductive glass electrode.

[0053] According to some embodiments of the present invention, in the electrochemical polymerization reaction, the electrodeposition method is constant potential method, constant current method or cyclic voltammetry method.

[0054] According to some embodiments of the present invention, the electrochemical polymerization reaction is carried out under a protective gas atmosphere.

[0055] In some embodiments of the present invention, the protective gas is selected from argon.

[0056] In some embodiments of the present invention, the DAD type polymer film material of the present invention is obtained by electro-deposition on the working electrode using a constant potential method. Preferably, the constant potential used is 1.15V-1.5V, such as about 1.2V, about 1.3V or about 1.4V; the deposition time is 20s-50s; such as about 30s or 40s.

[0057] The third aspect of the present invention provides an electrochromic material, which comprises the deuterium-containing polymer of the first aspect of the present invention or the deuterium-containing polymer prepared by the method of the second aspect.

[0058] The fourth aspect of the present invention provides use of the deuterium-containing polymer of the first aspect of the present invention or the deuterium-containing polymer prepared by the method of the second aspect in preparing an electrochromic device.

[0059] According to some embodiments of the present invention, the electrochromic device includes one or both of a display device and a light-transmitting device; further preferably, the electrochromic device includes at least one of a display, electrochromic glass, a smart window or a rearview mirror.

[0060] The present invention has at least the following beneficial effects:

[0061] The polymer of the present invention is based on a polymer containing a deuterium element acceptor unit, that is, a deuterium atom, which is an isotope of hydrogen element, is introduced into the benzene ring or anthracene ring of the electron acceptor unit (deuterated benzene ring or anthracene ring is used as the acceptor unit), and a thienyl derivative is used as the terminal donor unit. Since the deuterium atom has strong chemical stability, replacing the hydrogen atom with the deuterium atom can reduce the participation of the benzene ring or anthracene ring in the electrochemical reaction, thereby improving the stability of the polymer. Moreover, the deuterium-containing polymer of the present invention has good electrochromic performance under different voltages, such as fast response time, good optical transmittance, high coloring efficiency and good stability, and has a wide range of applications in the preparation of electrochromic devices.

[0062] In summary, the present invention provides a polymer based on a deuterium element acceptor unit. The presence of deuterium can reduce the reactivity of the polymer material in a chemical reaction or high temperature environment, thereby enhancing the chemical stability of the polymer; at the same time, the conjugated polymer of the present invention, which combines the deuterium atom-containing acceptor with a donor unit with a strong electron-donating ability, exhibits a faster response time (T ox =0.1s) and higher coloring efficiency (613.8cm 2 ·C -1 ). BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 The 4D-EDOT active precursor of Example 1 was prepared in DCM-Bu4NPF6 (0.1 mol·L -1 ) diagram of electrochemical polymerization in the system.

[0064] Figure 2 The polymer P(4D-EDOT) of Example 1 was dissolved in MeCN-Bu4NPF6 (0.1 mol·L -1 ) system.

[0065] Figure 3 This is the transmittance-time curve of the polymer P(4D-EDOT) in Example 1.

[0066] Figure 4 The polymer P (EDOT-Ph-EDOT) of Comparative Example 1 was dissolved in MeCN-Bu4NPF6 (0.1 mol·L -1 ) system.

[0067] Figure 5 This is the transmittance-time curve of the polymer P (EDOT-Ph-EDOT) of Comparative Example 1.

[0068] Figure 6 The polymer P (4AhD-EDOT) of Example 2 was dissolved in MeCN-Bu4NPF6 (0.1 mol·L -1 ) system.

[0069] Figure 7 This is the transmittance-time curve of the polymer P(4AhD-EDOT) of Example 2. DETAILED DESCRIPTION

[0070] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0071] Unless otherwise indicated herein, recitation of ranges of values ​​herein is merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, and each separate value is incorporated into the specification as if it were individually recited herein. Unless otherwise indicated herein, all exact values ​​provided herein represent corresponding approximate values ​​(e.g., all exact exemplary values ​​provided with respect to a particular factor or measurement can be considered to also provide corresponding approximate measurements, modified by "about" where appropriate).

[0072] As used herein, when used in connection with a numerical value, the term "about" is intended to include a set or range of numerical values. For example, "about" means a numerical range of ±5%, ±2%, ±1%, ±0.5%, ±0.2% or ±0.1% of the numerical value. In one embodiment, the term "about" refers to a numerical range of 5% more or less than a specific value. In another embodiment, the term "about" refers to a numerical range of 2% more or less than a specific value. In another embodiment, the term "about" refers to a numerical range of 1% more or less than a specific value.

[0073] The test methods used in the examples are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial sources. Unless otherwise specified, the same parameter values ​​in each example are the same. The examples described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0074] It should be noted that, in the embodiments of the present invention, the coloring efficiency refers to the ratio of the change in absorbance of the electrochromic material at a given wavelength to the total electron injection or extraction.

[0075] For an electrochromic material, the coloring efficiency CE (cm 2 ·C -1 ) is an important parameter for evaluating material performance. The study of coloring efficiency of conductive polymers should combine the electrochemical and spectral changes of electrochromic films, among which Q d (C·cm -2 ) refers to the amount of charge that moves in / out per unit area, and its calculation formula is as follows:

[0076] CE=ΔOD / Q d ;

[0077] The change in optical contrast (ΔOD) is the change in optical contrast at a specific wavelength λ. max Under the condition of electrochemical oxidation and reduction, the corresponding transmittance ratio of the polymer membrane (the transmittance of the polymer membrane in the doped state T ox (%) and the transmittance T in the neutral state red The logarithmic value of the ratio (%) is calculated by the following formula:

[0078] ΔOD=log(T ox / T red ).

[0079] Example 1

[0080] Electrochemical synthesis of polymer P(4D-EDOT):

[0081] (1) Synthesis of 4D-EDOT active precursor:

[0082]

[0083] Under nitrogen atmosphere, 1,4-dibromobenzene-2,3,5,6-deuterium (2.08mmol, 0.5g), tributyl (2,3-dihydro [3,4-b] [1,4] dioxin-5-yl) stannane (5.20mmol, 2.25g), and catalyst Pd (PPh3) 4 (0.08mmol, 0.096g) were placed in a 250mL single-necked flask, and DMF (20mL) and dry toluene (80mL) were added and stirred evenly, and heated to 120℃ for condensation and reflux reaction for 48 hours. After the system was cooled, the product was poured into saturated brine, extracted with dichloromethane 4 to 5 times, and then a small amount of water was added to wash the organic layer, and then the solvent was removed by reduced pressure distillation and rotary evaporation, and separated by silica gel chromatography column, the eluent was (DCM: PE = 1: 2), and the light yellow powder product 4D-EDOT was purified, and the yield was 67%.

[0084] (2) Electrochemical polymerization of polymer P(4D-EDOT):

[0085]

[0086] Under the protection of argon atmosphere, electrochemical polymerization was carried out in a three-electrode system, with a silver / silver chloride electrode as a reference electrode, a platinum wire as a counter electrode, and a glassy carbon as a working electrode; 10 mL of dichloromethane was used as a solvent, 4D-EDOT (0.00362 g, 0.01 mmol) was used as a polymerization monomer, and a mixed solution of 10 mL of acetonitrile and tetrabutylammonium hexafluorophosphate (0.3874 g, 1 mmol) was used as a supporting electrolyte solution. The polymerization was carried out in a monomer solution containing an electrolyte using a constant potential method, with a polymerization potential of 1.15 V, a scan rate of 100 mV / s, and a deposition time of 50 s. The polymer film obtained by electrodeposition was soaked and rinsed with acetonitrile to remove the electrolyte solution and precursor in the polymer to obtain a polymer P (4D-EDOT).

[0087] in, Figure 1 It shows that the 4D-EDOT active precursor (0.0005 mol·L -1 ) in the monomer solution DCM-Bu4NPF6 (0.1 mol·L -1 ) system, it can be seen that 4D-EDOT has good electrochemical polymerization behavior.

[0088] Electrochromic performance research:

[0089] (1) Test polymer P(4D-EDOT) in MeCN-Bu4NPF6 (0.1 mol·L -1 ) system, such as Figure 2As shown, the color change of the polymer material is observed with the naked eye. It can be seen that with the increase of potential, the color of the polymer material changes from dark yellow to gray-blue (dark yellow in the completely dedoped state). This is because the neutral polymer material has an absorption peak in the purple light region and the red light region, and the color of the neutral polymer material is dark yellow; after the polymer material is oxidized, the absorption peak in the purple light region gradually weakens, and the absorption peak in the red light region gradually weakens, and finally disappears completely; therefore, the polymer material in the completely dedoped state appears dark yellow, and the doped polymer material appears gray-blue.

[0090] (2) The transmittance-time curves of the polymer P(4D-EDOT) at wavelengths of 460 nm, 675 nm and 1100 nm were tested. The response time and coloring efficiency calculated from the time-transmittance curves are shown in Table 1, where T red is the transmittance of the polymer film in neutral state, T ox is the transmittance of the polymer film in the doped state, ΔT = T red -T ox As can be seen from Table 1, the polymer P(4D-EDOT) has a fast response time and high coloring efficiency.

[0091] Table 1 Electrochromic parameters of polymer P(4D-EDOT)

[0092]

[0093] The optical transmittance of P(4D-EDOT) was studied by timed absorption method at wavelengths of 460nm, 675nm and 1100nm. During the experiment, the time interval of the potential step change was 5s. Figure 3 As shown. At three specific wavelengths, the polymer material exhibits a certain optical contrast and good optical stability; in addition, the optical transmittance has a great influence on the color change of the polymer material, and the polymer material can be transformed from dark yellow in a completely dedoped state to gray-blue in a doped state.

[0094] Example 2

[0095] Electrochemical synthesis of polymer P(4AhD-EDOT):

[0096] (1) Synthesis of 4AhD-EDOT active precursor:

[0097]

[0098] Under nitrogen atmosphere, 9,10-dibromoanthracene-1,2,3,4,5,6,7,8-deuterium (1.45 mmol, 0.5 g), tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane (3.22 mmol, 1.201 g), and catalyst Pd(PPh3)4 (0.06 mmol, 0.04 g) were placed in a 250 mL single-necked flask, DMF (20 mL) and dry toluene (80 mL) were added and stirred evenly, and the mixture was heated to 120 °C and refluxed for 48 hours. After the system was cooled, the product was poured into saturated brine and extracted with dichloromethane for 4 to 5 times. A small amount of water was added to wash the organic layer. The solvent was then removed by reduced pressure distillation and rotary evaporation. The product was separated by a silica gel chromatography column with an eluent of (DCM: PE = 1: 2) to obtain an orange-red solid 4AhD-EDOT with a yield of 58.7%.

[0099] (2) Synthesis of polymer P(4AhD-EDOT):

[0100]

[0101] Under argon atmosphere, electrochemical polymerization was carried out in a three-electrode system, with a silver / silver chloride electrode as a reference electrode, a platinum wire as a counter electrode, and a glassy carbon as a working electrode; 10 mL of dichloromethane was used as an electrolyte, 4AhD-EDOT (0.00466 g, 0.01 mmol) was used as a polymerization monomer, and 10 mL of a mixed solution of acetonitrile and tetrabutylammonium hexafluorophosphate (0.3874 g, 1 mmol) was used as a supporting electrolyte; the polymerization was carried out by a constant potential method, with a polymerization potential of 1.08 V, a scan rate of 100 mV / s, and a deposition time of 50 s. The polymer film obtained by electrodeposition was soaked and rinsed with acetonitrile to remove the electrolyte solution and precursor in the polymer to obtain a polymer P (4AhD-EDOT).

[0102] Electrochromic performance research:

[0103] The test polymer P(4AhD-EDOT) was prepared in MeCN-Bu4NPF6 (0.1 mol·L -1 ) system, such as Figure 6 As shown in the figure, combined with the color change of the polymer material observed with the naked eye, it can be seen that with the increase of the potential, the color of the polymer material changes from yellow to blue (yellow in the completely dedoped state). This is because the neutral polymer material has an absorption peak in the purple light region and the red light region respectively, and the color of the neutral polymer material appears yellow; after the polymer material is oxidized, the absorption peak in the purple light region gradually weakens, the absorption peak in the red light region gradually weakens, and finally disappears completely.

[0104] The transmittance-time curves of the tested polymer P(4AhD-EDOT) at 522nm and 682nm are shown in Table 3. The response time and coloring efficiency calculated from the time-transmittance curves are shown in Table 3. As can be seen from Table 3, the polymer P(4AhD-EDOT) has a fast response time and high coloring efficiency.

[0105] Table 2 Electrochromic parameters of polymer P(4AhD-EDOT)

[0106]

[0107]

[0108] The optical transmittance of P(4AhD-EDOT) was studied by chronoabsorption method at wavelengths of 522nm and 682nm. During the experiment, the time interval between potential step changes was 5s. Figure 7 As shown. At three wavelengths, the polymer material exhibits a certain optical contrast and good optical stability; in addition, the optical transmittance has a great influence on the color change of the polymer material, and the polymer material can be transformed from yellow in a completely dedoped state to blue in a doped state.

[0109] Example 3

[0110] Electrochemical synthesis of polymer P(4D-ProEDOT):

[0111] (1) Synthesis of 4D-ProEDOT active precursor:

[0112]

[0113] Under nitrogen atmosphere, 1,4-dibromobenzene-2,3,5,6-deuterium (2.08 mmol, 0.5 g), tributyl(3,3-didecyl-3,4-dihydro-2H-thiophene[3,4-b][1,4]dioxepin-6-yl)tin (4.30 mmol, 1.52 g), and catalyst Pd(PPh3)4 (0.08 mmol, 0.096 g) were placed in a 250 mL single-necked flask, DMF (20 mL) and dry toluene (80 mL) were added and stirred evenly, and the mixture was heated to 120°C and refluxed for 48 hours. After the system was cooled, the product was poured into saturated brine and extracted with dichloromethane for 4 to 5 times. A small amount of water was added to wash the organic layer. The solvent was then removed by reduced pressure distillation and rotary evaporation. The product was separated by a silica gel chromatography column with an eluent of (DCM: PE = 1:2) and purified to obtain a light yellow powder product 4D-ProEDOT with a yield of 48.3%.

[0114] (2) Synthesis of polymer P(4D-ProEDOT):

[0115]

[0116] Under argon atmosphere, electrochemical polymerization was carried out in a three-electrode system, with a silver / silver chloride electrode as a reference electrode, a platinum wire as a counter electrode, and a glassy carbon as a working electrode; 10 mL of dichloromethane was used as the electrolyte, 4D-ProEDOT (0.00951 g, 0.01 mmol) was used as the polymerization monomer, and 10 mL of a mixed solution of acetonitrile and tetrabutylammonium hexafluorophosphate (0.3874 g, 1 mmol) was used as the supporting electrolyte; the polymerization was carried out by a constant potential method, with a polymerization potential of 1.2 V, a scan rate of 100 mV / s, and a deposition time of 50 s. The polymer film obtained by electrodeposition was soaked and rinsed with acetonitrile to remove the electrolyte solution and precursor in the polymer to obtain a polymer P (4D-ProEDOT).

[0117] Example 4

[0118] Electrochemical synthesis of polymer P(4AhD-ProEDOT):

[0119] (1) Synthesis of 4AhD-ProEDOT active precursor:

[0120]

[0121] Under nitrogen atmosphere, 9,10-dibromoanthracene-1,2,3,4,5,6,7,8-deuterium (1.45 mmol, 0.5 g), tributyl(3,3-didecyl-3,4-dihydro-2H-thiophene[3,4-b][1,4]dioxepin-6-yl)tin (4.30 mmol, 1.52 g), and catalyst Pd(PPh3)4 (0.029 mmol, 0.025 g) were placed in a 250 mL single-necked flask, DMF (20 mL) and dry toluene (80 mL) were added and stirred evenly, and the mixture was heated to 120°C and condensed under reflux for 48 hours. After the system was cooled, the product was poured into saturated brine and extracted with dichloromethane for 4 to 5 times. A small amount of water was added to wash the organic layer. The solvent was then removed by reduced pressure distillation and rotary evaporation. The product was separated by silica gel chromatography with an eluent of (DCM: PE = 1: 2) to obtain a red solid 4AhD-ProEDOT with a yield of 45.0%.

[0122] (2) Synthesis of polymer P(4AhD-ProEDOT):

[0123]

[0124] Under argon atmosphere, electrochemical polymerization was carried out in a three-electrode system, with a silver / silver chloride electrode as a reference electrode, a platinum wire as a counter electrode, and a glassy carbon as a working electrode; 10 mL of dichloromethane was used as an electrolyte, 4AhD-ProEDOT (0.01055 g, 0.01 mmol) was used as a polymerization monomer, and 10 mL of a mixed solution of acetonitrile and tetrabutylammonium hexafluorophosphate (0.3874 g, 1 mmol) was used as a supporting electrolyte; the polymerization was carried out by a constant potential method, with a polymerization potential of 1.05 V, a scan rate of 100 mV / s, and a deposition time of 50 s. The polymer film obtained by electrodeposition was soaked and rinsed with acetonitrile to remove the electrolyte solution and precursor in the polymer to obtain a polymer P (4AhD-ProEDOT).

[0125] Comparative Example 1

[0126] Electrochemical synthesis of polymer P(EDOT-Ph-EDOT):

[0127] (1) Synthesis of EDOT-Ph-EDOT active precursor:

[0128]

[0129] Under nitrogen atmosphere, 1,4-dibromobenzene (2.08mmol, 0.5g), tributyl (2,3-dihydro [3,4-b] [1,4] dioxin-5-yl) stannane (5.8mmol, 2.25g), and catalyst Pd (PPh3) 4 (0.08mmol, 0.096g) were placed in a 250mL single-necked flask, and DMF (20mL) and dry toluene (80mL) were added and stirred evenly, and heated to 120°C for condensation and reflux reaction for 48 hours. After the system was cooled, the product was poured into saturated brine, extracted with dichloromethane 4 to 5 times, and then a small amount of water was added to wash the organic layer, and then the solvent was removed by reduced pressure distillation and rotary evaporation, and separated by silica gel chromatography column, the eluent was (DCM: PE = 1: 2), and the light yellow powder product EDOT-Ph-EDOT was purified, and the yield was 74%.

[0130] (2) Synthesis of polymer P(EDOT-Ph-EDOT):

[0131]

[0132] Under the protection of argon atmosphere, electrochemical polymerization was carried out in a three-electrode system, with a silver / silver chloride electrode as a reference electrode, a platinum wire as a counter electrode, and a glassy carbon as a working electrode; 10 mL of dichloromethane was used as the electrolyte, EDOT-Ph-EDOT (0.00362 g, 0.01 mmol) was used as the polymerization monomer, and 10 mL of a mixed solution of acetonitrile and tetrabutylammonium hexafluorophosphate (0.3874 g, 1 mmol) was used as the supporting electrolyte; cyclic voltammetry was used for polymerization, with a polymerization potential of 1.15 V, a scan rate of 100 mV / s, and a deposition time of 50 s. The polymer film obtained by electrodeposition was soaked and rinsed with acetonitrile to remove the electrolyte solution and precursor in the polymer to obtain a polymer P (EDOT-Ph-EDOT).

[0133] Electrochromic performance research:

[0134] (1) Test polymer P(EDOT-Ph-EDOT) in MeCN-Bu4NPF6 (0.1 mol·L -1 ) system, such as Figure 4 As shown in the figure, combined with the color change of the polymer material observed with the naked eye, it can be seen that with the increase of the potential, the color of the polymer material changes from dark red to blue (dark red in the completely dedoped state). This is because the neutral polymer material has an absorption peak in the purple light region and the red light region respectively, and the color of the neutral polymer material appears dark red; after the polymer material is oxidized, the absorption peak in the purple light region gradually weakens, and the absorption peak in the red light region gradually weakens, and finally disappears completely; therefore, the polymer material in the completely dedoped state appears dark red, and the doped polymer material appears blue.

[0135] (2) The transmittance-time curves of the polymer P (EDOT-Ph-EDOT) at wavelengths of 460 nm, 675 nm and 1100 nm were tested. The response time and coloring efficiency calculated from the time-transmittance curves are shown in Table 2.

[0136] Table 2 Electrochromic parameters of P(EDOT-Ph-EDOT)

[0137]

[0138] The optical transmittance of P(EDOT-Ph-EDOT) was studied by chronoabsorption method at wavelengths of 460nm, 700nm and 1100nm. During the experiment, the time interval of the potential step change was 5s. Figure 5As shown. At three specific wavelengths, the polymer material exhibits a certain optical contrast and good optical stability; in addition, the optical transmittance has a great influence on the color change of the polymer material, and the polymer material can be transformed from dark red in a completely dedoped state to blue in a doped state.

[0139] Comparison of Example 1 and Comparative Example 1 shows that replacing H atoms with deuterium atoms can make (P4D-EDOT) show significantly improved color rendering efficiency (123.5 cm 2 ·C -1 ) and a higher optical contrast (ΔT = 34.0%). The introduction of deuterium isotopes is expected to expand the polymer to the field of near-infrared OLEDs, thereby enhancing the potential of near-infrared OLED performance, which will provide an effective strategy for the development of electrochromic fields in the near-infrared region. At the same time, it can be seen from Example 2 that the coloring efficiency of the deuterium-containing polymer prepared by the present invention at wavelengths of 522nm and 682nm can reach 360.7cm 2 C -1 、613.8cm 2 C -1 , wherein the redox switching time at 682 nm is even less than 1.0 s, indicating that the deuterium-containing polymer of the present invention has excellent electrochromic performance, especially in terms of coloring efficiency and response time.

[0140] As can be seen from the above, the polymer of the present invention is a polymer based on a deuterium acceptor unit, that is, a deuterium atom, an isotope of hydrogen element, is introduced into the benzene ring or anthracene ring of the electron acceptor unit, and a thienyl derivative is used as the terminal donor unit. Since deuterium atoms have strong chemical stability, replacing hydrogen atoms with deuterium atoms can reduce the participation of benzene rings or anthracene rings in electrochemical reactions, thereby improving the chemical stability of the polymer. Moreover, the deuterium-containing polymer of the present invention has good electrochromic properties, such as fast response time, good optical transmittance, high coloring efficiency, etc., and has a wide range of applications in the preparation of electrochromic devices.

[0141] In summary, the present invention provides a polymer based on a deuterium-containing acceptor unit. The presence of deuterium can reduce the reactivity of the polymer material in a chemical reaction or high temperature environment, thereby enhancing the chemical stability of the polymer; at the same time, the conjugated polymer of the present invention, which combines the deuterium-containing acceptor with a donor unit with a strong electron-donating ability, exhibits a faster response time (T ox =0.1s) and higher coloring efficiency (613.8cm 2 ·C -1 ).

[0142] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A deuterium-containing polymer, characterized in that Having a structure as shown in any one of formula (I) to formula (IV): In formulas (I) to (IV), X1 to X4 are each independently O, S, or Se; Y1 to Y8 are each independently O or S; R1 to R4 are each independently C2 to C 12 Alkyl; n1-n4 are each independently 3-200.

2. The deuterium-containing polymer according to claim 1, characterized in that In formulas (I) to (IV), X1 to X4 are each independently S; and / or, Y1-Y8 are each independently O; and / or, R1 to R4 are each independently C5 to C 10 alkyl.

3. The deuterium-containing polymer according to claim 2, characterized in that The deuterium-containing polymer has a structure as shown in any one of formulas (1) to (4): In formulae (1) to (4), n1 to n4 are each independently 3 to 200.

4. A method for preparing a deuterium-containing polymer as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: The active precursor of the deuterium-containing polymer is subjected to an electrochemical polymerization reaction to obtain the deuterium-containing polymer, wherein the active precursor of the deuterium-containing polymer has a structure shown in any one of formula (I') to formula (IV'): In formulae (I') to (IV'), X1 to X4, Y1 to Y8 and R1 to R4 are as defined in any one of claims 1 to 3.

5. The method according to claim 4, characterized in that The preparation method of the active precursor comprises: in the presence of a catalyst, performing a cross-coupling reaction on an acceptor compound and a donor compound in a solvent to obtain the active precursor; The receptor compound is: The donor compound is: The catalyst includes tetrakistriphenylphosphine palladium and / or bistriphenylphosphine palladium dichloride; The solvent includes at least one of benzene, toluene or N,N-dimethylformamide.

6. The method according to claim 4, characterized in that The electrochemical polymerization reaction includes using a solution containing the active precursor as an electrolyte solution, performing electrodeposition in a three-electrode system consisting of a reference electrode, a counter electrode and a working electrode, and obtaining the polymer on the working electrode; the reference electrode is selected from an Ag / AgCl electrode; the counter electrode is selected from a platinum electrode; and the working electrode is selected from a Pt, glassy carbon or ITO conductive glass electrode.

7. The method according to claim 6, characterized in that The solvent of the electrolyte solution includes at least one of dichloromethane, chloroform or acetonitrile; And / or, the electrolyte solution further contains a supporting electrolyte; the supporting electrolyte includes at least one of tetrabutylammonium hexafluorophosphate, tetrabutylammonium tetrafluoroborate or lithium perchlorate.

8. The method according to claim 7, characterized in that In the electrolyte solution, the concentration of the active precursor is 0.0005-0.01 mol·L -1 ; and / or, the concentration of the supporting electrolyte is 0.01 to 0.2 mol·L -1 .

9. An electrochromic material, characterized in that: The deuterium-containing polymer comprises the deuterium-containing polymer according to any one of claims 1 to 3 or the deuterium-containing polymer prepared by the method according to any one of claims 4 to 8.

10. Use of the deuterium-containing polymer according to any one of claims 1 to 3 or the deuterium-containing polymer prepared by the method according to any one of claims 4 to 8 in preparing an electrochromic device.

Citation Information

Patent Citations

  • Electrochromic polymer and synthesis and uses thereof

    CN110892001A

  • Electrochromic polymer with polar side chain

    CN113754867A

  • Ï€-electron conjugated polymer, and photoelectric conversion device

    JP2013189602A

  • Electrochromic element and manufacturing method of the same

    JP2015184632A

  • Battery pack and Vehicle including the same

    KR103019953B1